2021
DOI: 10.3390/su13169368
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Outcomes of a Participatory Research Study: Findings from an Environmental Epidemiological Study in Kaunas City

Abstract: The achievement of a sustainable urban environment and health for all requires the engagement and greater awareness of local communities on issues of environment and health. This HORIZON2020 CitieS-Health study presents the outcomes of the environmental epidemiological research on the participants’ acquisition of new skills and knowledge as well as on health behaviour. We conducted a cross-sectional study of 1062 residents of Kaunas city, Lithuania, from 2019 to 2021. We analysed the associations between the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(58 reference statements)
1
0
0
Order By: Relevance
“…Therefore, regular visit to green space may be beneficial for health. These our data are consistent with the results of the studies presenting that urban green spaces are associated with better general health and physical activity in green environment [ 79 , 80 ], and that improving the neighbourhood environment would promote increased physical activity, such as reaching green spaces by walking, might contribute to the well-being of urban residents [ 81 , 82 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, regular visit to green space may be beneficial for health. These our data are consistent with the results of the studies presenting that urban green spaces are associated with better general health and physical activity in green environment [ 79 , 80 ], and that improving the neighbourhood environment would promote increased physical activity, such as reaching green spaces by walking, might contribute to the well-being of urban residents [ 81 , 82 ].…”
Section: Discussionsupporting
confidence: 93%
“…The tools included in the Toolkit presented in this paper were mostly developed and used as part of the activities in the five pilot studies of the CitieS-Health project in Barcelona (Spain), Amsterdam (Netherlands), Lucca (Italy), Ljubljana (Slovenia), and Kaunas (Lithuania). This paper deals with the methodological description of the toolkit creation and described some use cases in real-life applications of the CitieS-Health project, while the specific activities carried out in the individual pilot studies, the results obtained and the lessons learned are given elsewhere (Grazuleviciene et al, 2020a;Grazuleviciene et al, 2020b;Kocman et al, 2020;Grazuleviciene et al, 2021a;Grazuleviciene et al, 2021b;Grazuleviciene et al, 2022;Gignac et al, 2022a;Gignac et al, 2022b;De Marchi et al, 2022). Substantial elements of this work have been reported in deliverables from the CitieS-Health project, and reused for the purpose of this paper, in particular D2.1 (Kocman et al, 2019), D5.2 (Balestrini et al, 2019) and D5.3 (Errandonea et al, 2022).…”
Section: Toolkit In the Context Of Cities-health Projectmentioning
confidence: 99%
“…With respect to SDG 11.5 which concerns disasters and their social impacts, Ranjbari et al built a fuzzy surface based on the experts' opinion and suggested that SDG 11.5 has the highest priorities for action to support the SDGs achievement post COVID-19 in Iran [11]. In addition, related investigations have also been executed by Regina, Taher, and Philipp according to the commutation of 11.6 and 11.7, respectively [12][13][14]. However, compared to these aforementioned social issues, another precious social resource mentioned in SDG 11.4, i.e., world cultural and natural heritage, have been investigated relatively seldomly.…”
Section: Introductionmentioning
confidence: 99%